SOSIALISASI PENTINGNYA USG MATERNAL UNTUK MENDETEKSI KEJADIAN STUNTING DI KELURAHAN STERIO KABUPATEN BANYUASIN - Rizka Muliani; Muslimah Putri Utami; J. Sigalingging Sigalingging; Leni Noviyanti; Riki Rinaldi; Irdan Irdan (Institut Pendidikan Tapanuli Selatan, 2022)
Condition at birth is one of the important birth parameters in evaluating the condition of a healthy baby. Stunting at birth is associated with a higher risk of stunting in childhood and adulthood. The health and nutritional status of women during pregnancy affect the health of their babies. Stunting or chronic malnutrition, which is characterized by abnormal height in children, can be prevented during pregnancy. This can be done by detecting stunting through routine ultrasound examinations. Regular check-ups on pregnant women can help determine whether the growth of the fetus is in accordance with age. In an effort to prevent stunting, the Faculty of Health, Universitas Kader Bangsa, Palembang held counseling for residents of the Sterio sub-district, Banyuasin Regency to routinely carry out Maternal Ultrasound. The purpose of this activity is to increase knowledge, especially for pregnant women and mothers who have infants under five to be able to take advantage of existing health services at the Puskesmas to conduct ultrasound examinations for early detection of stunting. The implementation method in the community service program is through providing counseling about the importance of Maternal USG to detect stunting to mothers in the Sterio sub-district area, Banyuasin Regency through 3 (three) stages, namely implementation strategy meetings, site surveys, then preparation of facilities and infrastructure. The ability of participants in mastering the material can be said to be good (75%). Submission of material using lecture and demonstration methods supports the participants' ability to master the material. Through this activity, there was an increase in participants' knowledge of early detection of stunting, in this case anthropometric examination of infants and toddlers. Prevention of stunting in children under five in the village of Sterio is expected to be realized optimally with outreach activities.